AN ANALYSIS OF THE EFFECT OF CURRENCY MISMATCH ON A COUNTRY’S DEFAULT RISK - Jankovic, Irena; Zivkovic, Bosko (Economic Annals, 2014)
The aim of this paper is the measurement of currency mismatch for a selected group of developing and frontier markets in the Central and Eastern Europe and Western Balkan regions and the analysis of the effects of aggregate currency misbalances on particular countries’ risk of default. The empirical tests provided confirm the positive effect of currency mismatch on default risk, which is reflected in the behaviour of yield spreads on the government bonds of the countries under consideration. The higher the negative currency misbalances are, the higher the EMBI spreads appear to be, and vice versa.